An overview of banana biomass as a potential renewable energy source in Malaysia - Abdul Mu’iz Abdul Razak; Raja Norizawati Raja Othman; Mohd Faizal Abdullah; Ku Zarina Ku Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2021)
Electricity is a vital component necessary to stimulate the growth of a country whereby Malaysia relies upon nonrenewable fossil fuel for much of its needs. Since the 70’s oil crisis, Malaysia has attempted to preserve its oil resources and increase the contribution of renewable energy which subsequently has boosted the rapid increase of renewable energy supply, particularly in hydropower but under the 5th Fuel Diversification policy, the country prioritises to diversify its fuel sources. Banana waste has been identified as one of the potential sources due to its abundance in natural resources in Malaysia for being widely planted in agricultural sector. It has been used by neighbouring country, namely Thailand and also efficiently recycled by developed nations worldwide. This paper will discuss the potential biomass feedstock, and banana plant is chosen for the nature of its abundance, fast growth rate, and disposal after harvest. Conversion from biomass into energy can be done by direct combustion, solid biomass briquette, bioethanol, and biogas. Theoretically, all the methods except direct combustion are viable for energy generation but bioethanol and biogas suffer from compatibility issues with existing infrastructure designed for fossil fuel thus making solid fuel a topic that should be researched further to improve its uses in cogeneration and boilers. Hence, banana biomass is feasible for use as a source of renewable energy in Malaysia.